PERBEDAAN RERATA KADAR NATRIUM MATERNAL ANTARA PREEKLAMPSIA BERAT DAN EKLAMPSIA DI RSUP DR. M. DJAMIL PADANG - Efri, Gunawan; Djanas, Dovy (Fakultas Kedokteran Universitas Andalas, 2018)
Objective: To determine the difference in mean ratio of sodium content between pregnancy with severe preeclampsia and eclampsia.Method: This is an analytical study using a cross sectional study design. The study was conducted inMaternity room of Dr. M. Djamil Padang from January 15th, 2016 to December 31st, 2017, there were 60 patients as subjects, the sample was divided into 2 groups: severe preeclampsia and eclampsia. Furthermore, history and physical examination to obtain data and clinical diagnosis. Data is recorded in a research form that has been provided, then performed blood electrolytes of Sodium and Potassium. Statistical analysis to assess significance using T-test.Results: In the severe preeclampsia and eclampsia, multiparous parity had the highest respondent. This is consistent with the literature in which the incidence of preeclampsia is more common in late pregnancy.Conclusions: There was no significant difference in the mean sodium ratio between normal severe preeclampsia pregnancy and normal pregnancy.Keywords: pregnancy condition, severe preeclampsia, eclampsia, and sodium.